Knowledge, attitude, perceived barriers, and practices among pharmacists regarding risk assessment of cardiovascular disease: a cross-sectional study in Yemen - Al-Ashwal, Fahmi Y.; Syed Sulaiman, Syed Azhar; Sheikh Ghadzi, Siti Maisharah; Kubas, Mohammed Abdullah; Halboup, Abdulsalam (Taylor & Francis, 2022)
Background Risk evaluation of atherosclerotic cardiovascular diseases can guide the decision-making on various preventive measures, such as initiating or deferring statin therapy. Pharmacists can play an active part in the risk evaluation and primary prevention of atherosclerotic cardiovascular diseases. Thus, our study aimed to assess the pharmacists knowledge, attitude, perceived barriers, and practices regarding risk assessment of atherosclerotic cardiovascular disease. Materials and methods A cross-sectional study was conducted among 500 pharmacists using a structured validated questionnaire between November 2020 and February 2021. The Mann-Whitney and Kruskal-Wallis tests were used to analyze the data. Results A total of 456 pharmacists completed the questionnaire out of 500 distributed (91.2% response rate). Over 60% of participants responded with never or rarely for two out of five cardiovascular diseases (CVD) prevention practices. The lowest pharmacist-patient counseling practices were for side effects of statin medication (14.5%) and reviewing the patients medications to avoid potential statin-drug interactions (31.8%). Participants had a high positive attitude (median = 34 out of 40). The three major barriers for risk assessment were the lack of support (74.8%), the lack of resources (70.6%), and inadequate training (48.7%). Interestingly, having ?75 customers a day, community pharmacies, PharmD degree, age ?30?years, and experience ?6 years were significantly associated (p < .05) with higher CVD prevention activities and counseling practices. Conclusion Pharmacists have a high positive attitude toward CVD risk assessment. However, they had insufficient knowledge and only provided limited activities and counseling services for CVD prevention and statin therapy. Participants perceived several barriers to CVD risk assessment services in pharmacies. Therefore, it is necessary to remove these impediments for pharmacists to be more involved in CVD risk assessment and prevention. Also, continuing medical education and adequate training for pharmacists are required.